Analysis of Errors and Complications in the Use of Endocal Structures Used in Dentistry - Islamova Nilufar Bustanovna; Abdulaxatov Abdug’affor Abdusattor o’g’li (Scientific Trends, 2024)
1. In clinical practice, in 77.2 ± 2.8% of cases, various clinical errors and complications occurred during the restoration of defects in the crown part of sc teeth. Molar was less detected in the recovery of SC defects in solid tissue (75.2 ± 2.5%) and premolecular (76.5 ± 2.3%) with significantly higher levels of errors and complications in the recovery of SC defects, and sc defects in the coronary coronary part. teeth (64, 5 ± 2.3%). 2. High indicators of defect levels of completed SC treatment are determined (1,67 ± 0.08). Significantly large indicators of completed treatment defects were detected in the lower jaw (1.84 ± 1.07), defects in the corronal part of the teeth (0.64 ± 0.04), sc teeth during crown restoration. premolars (1,78 ± 0.05) and molars (1,80 ± 0.11). 3. The methodological approaches we propose will help prevent and eliminate clinical errors and complications in the treatment of patients with dental structures with severe dental defects.